2008
DOI: 10.2139/ssrn.1122804
|View full text |Cite
|
Sign up to set email alerts
|

Private Supplementary Tutoring in Turkey Recent Evidence on its Various Aspects

Abstract: Abstract:This paper first describes the educational system in Turkey an the two national examinations for advancing upper levels of schooling which give raise to the demand for private tutoring called "dersane" in Turkish. Second, the evolution of the Private tutoring Centers (PTC) are described and compared with the high schools in the country. Third, geographical distribution of the PTC, general high schools and the proportion of high school age population are compared over the provinces to give an idea abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
(11 reference statements)
0
13
0
2
Order By: Relevance
“…South Korea is a particularly prominent example here: the nation's total household expenditure for supplementary tutoring in 2006 was estimated at 24 billion USD, or 2.8% of GDP (Kim & Lee, 2010). Turkey's estimated supplementary tutoring expenditure in 2004 was 2.9 billion USD, equivalent to 0.96% of gross national product (Tansel & Bircan, 2006). In 2002, Egypt estimated that Egyptian families spend around 18 million USD on supplementary tutoring each year before college, equivalent to 1.6% of GDP (The World Bank, 2002).…”
Section: B Research On Supplementary Tutoring Expenditures For Compumentioning
confidence: 99%
“…South Korea is a particularly prominent example here: the nation's total household expenditure for supplementary tutoring in 2006 was estimated at 24 billion USD, or 2.8% of GDP (Kim & Lee, 2010). Turkey's estimated supplementary tutoring expenditure in 2004 was 2.9 billion USD, equivalent to 0.96% of gross national product (Tansel & Bircan, 2006). In 2002, Egypt estimated that Egyptian families spend around 18 million USD on supplementary tutoring each year before college, equivalent to 1.6% of GDP (The World Bank, 2002).…”
Section: B Research On Supplementary Tutoring Expenditures For Compumentioning
confidence: 99%
“…Silova et al (2006) showed that in Azerbaijan, 93% of the respondents reported that they had received private tutoring in the form of lessons or courses during their final year of secondary school; 80% reported receiving such tutoring in Georgia; 79% in Ukraine; 71% in Mongolia; 66% in Poland; and 56% in Slovakia. In Turkey, private tutoring called dersane was examined in relation with national examinations for advancing to upper levels of schooling (Tansel and Bircan 2008). In England, U.K., estimates suggest that 27% of primary and secondary school students had a private tutor for exams and help with daily learning (Ireson and Rushforth 2004).…”
Section: Worldwide Shadow Educationmentioning
confidence: 99%
“…One of the most widespread assumptions is that extensive PT exists in countries with competition for future educational opportunities, which is usually accompanied by a ''tight linkage'' between academic performance and later opportunities in higher education and the labor market (Baker and Letender 2005;Silova and Bray 2006). For instance, the solid alliance between elite colleges and future job prospects in South Korea and Taiwan, the examination-based link between secondary schools and prestigious colleges in Greece, the highly competitive higher education entrance examinations in Turkey, and the secondary school selection process in Japan provide a strong explanation for why students use PT (e.g., Stevenson and Baker 1992;Kim and Lee 2001;Bray and Kwok 2003;Tansel and Bircan 2008). In these circumstances, high-stakes examinations serve as ''a gatekeeper to education and labor market opportunities'' (Baker and Letender 2005, p. 62).…”
Section: Review Of Literaturementioning
confidence: 99%